Software implementation of side-channel analysis on AES encryption with different key length - Heng, Denley Jing Jie (Nanyang Technological University, 2022)
Cryptographic algorithms such as Advanced Encryption Standard (AES) are usually strong against mathematical attacks even with a huge amount of computing power. However, correlated information such as power consumption and electromagnetic emissions is leaked when the algorithms are implemented on a physical device. This leads to side-channel attacks (SCA) which can be used for exploiting the leakage to recover the cryptographic key. In order to increase the resistance against side-channel attacks, one way is to increase the key search complexity of encryption by increasing the key length. The implementation of stronger AES encryption such as 192-bit and 256-bit will be investigated. Furthermore, software implementation of side-channel analysis will be extended from AES 128 to AES 192/256 to extract the different round keys.